PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ANGKASA PURA II - Mulia Indah Purwati; Efandri Agustian (STEKOM PRESS, 2023)
style and work motivation on employee performance at PT. ANGKASA PURA II JAMBI. The sample in this study are employees at PT. ANGKASA PURA II JAMBI The method used in this research is the quantitative method by performing multiple linear regression analysis. This research was conducted with quantitative methods. The data collection technique used is a questionnaire. The data analysis technique used in this study is multiple linear regression using SPSS version 16 for windows.Leadership style partially has a significant effect on employee performance, partially work motivation also has a significant effect on employee performance. Leadership style and work motivation simultaneously affect employee performance.